Pleistocene glaciations of the northern Alpine Foreland - M. Fiebig; F. Preusser (Geographica Helvetica)
It is now well known that climate and environment are not stable over geological time and Alpine Quaternary stratigraphy has widely evolved since the first discussions on Pleistocene glaciations nearly two centuries ago. Originally, in the late 19th century, three and later four glacial periods were postulated but with more research it appears that several more cold phases and separate ice advances occurred. To solve the history of climate and environmental change, a reliable time frame for the available geomorphological evidence is necessary. While some very interesting results have been presented in recent years, the amount of numerical dating is still very small and needs to be improved in order to unravel the full story of the Alpine palaeoclimate.